Activation of Murine Macrophages. (2nd November 2015) - Mosser, David M.; Gonçalves, Ricardo
Abstract: Our understanding of cell‐mediated immunity (CMI) has revealed the importance of activated macrophages as key immune effector cells. Over the past decade, we have come to realize that macrophages exhibit remarkable plasticity, and different populations of macrophages with distinct physiologies can develop in response to different stimuli. In fact, it is likely that the number of different macrophage populations that can arise may be as diverse as the activating stimuli that induce them. Some of these stimuli can instruct macrophages to kill microbes (classical activation), lay down extracellular matrix components to promote wound healing (alternative activation), or secrete anti‐inflammatory cytokines to terminate inflammation (regulatory macrophages). New ways to biochemically identify these cells have led to a better understanding of the heterogeneity of activated macrophages. As our understanding of the various macrophage populations increases, so does the potential for therapeutic intervention based on targeting specific populations of activated macrophages. © 2015 by John Wiley & Sons, Inc.